Reliability Analysis and Maintenance Strategy Optimization of Subway Station Platform Screen Door System - WEI Donghua; LI Zhengzhong; LI Li; LI Sheng (Chengshi guidao jiaotong yanjiu)
[Objective] As an important passage for passengers to get on and off the train, the platform screen door (PSD) plays a crucial role in passenger safety. To ensure the safe and stable operation of the PSD system, a reliability analysis of this system is carried out based on fault data, and its maintenance strategy is optimized and adjusted as per analysis results. [Method] Based on the fault data of subway station PSD of a certain Tianjin subway line from 2018 to 2021, and combined with the structure and function of the PSD system, common failures of the PSD system are classified and counted. The system reliability function is determined through methods like mathematical statistics and fault distribution fitting. With the goal of minimizing the equipment average maintenance cost, a maintenance cycle optimization model is constructed under reliability constraints to optimize the PSD system maintenance strategy. [Result & Conclusion] According to fault data fitting results, the fault distribution of both the PSD mechanical system and the electrical system obey the Weibull distribution. Under the existing equipment operation status, the optimal maintenance cycle of the PSD mechanical system is 20 days, and that of the electrical system is 7 days. Therefore, the PSD system maintenance strategy can be adjusted to a three-week whole system inspection with weekly electrical system inspections.